Parenting Styles and Secondary School Students’ Attitudes towards Islamic Studies in Kwara Central Senatorial District, Nigeria - Abdur-Rafiu, Jamiu; Ajidagba, U. A.; Adam, Zakariyau Salihu (NIU Journal of Social Sciences, 2018)
Abstract. The purpose of the study was to investigate the influence of parenting styles on secondary school students' attitude towards learning Islamic Studies in Kwara Central Senatorial District, Nigeria. Questionnaire and Pro-forma were used to collect data on parenting styles and students' attitude towards learning Islamic Studies. Simple random sampling technique was adopted to select 300 students across the sampled public schools. Four research questions were raised and three null hypotheses were formulated and tested in the study. The data collected were analyzed using frequency count Mean, Standard Deviation and Pearson Product Moment Correlation Co-efficient statistics to answer the research questions and test the hypotheses formulated in the study. The findings showed that most of the students disposed negatively to learning Islamic Studies. It was also found that parenting styles adopted have influence on the attitude of the students towards learning Islamic Studies. In addition, it was observed that students from authoritative parenting have positive attitude than students from other parenting styles. Based on the findings of the study, it was recommended that teachers should take cognizance of the fact that students are from various homes and with different parenting styles thereby catering for the individual differences that may affect their attitudes to learning Islamic Studies. Parents should adopt authoritative parenting style to enhance optimal performance of the students. In addition, there is also the need for provision of enlightenment for parents on the parenting style they should adopt in order to assist their children to dispose positively to learning. Key words: parenting styles, attitude, Islamic Studies, authoritarian, permissive, authoritative